The Relationship Between Health Literacy Level and Media Used as a Source of Health-Related Information - Seçil Özkan; Hakan Tüzün; Asiye Uğraş Dikmen; Nur Baran Aksakal; Deniz Çalışkan; Özge Taşçı; Selime Ceylan Güneş (SLACK Incorporated, 2021)
Background: Previous studies have not shown the level of health literacy or associated factors on a national level in Turkey using a scale that has been adapted to the country and its culture. Objective: This study aimed to determine health literacy levels in Turkey and to investigate the association of health literacy with socioeconomic factors as well as with the instruments used as sources of health-related information. Methods: This cross-sectional, nationally representative study was conducted using a computer-assisted personal interview approach and included 6,228 households (response rate, 70.9%). The Turkey Health Literacy Scale was used to measure health literacy. Sources of health-related information, such as newspapers, television, internet, and smartphones, were included in the regression model for health literacy. Key Results: The proportion of participants with inadequate and problematic health literacy was 30.9% and 38%, respectively, showing that approximately 7 of 10 participants had limited health literacy. The frequencies of inadequate and problematic health literacy were higher in the disease prevention and promotion domains (37.4% and 34.2%, respectively) compared with those in the health care domain (27.1% and 31.3%, respectively). The most frequently used medium as a source of health-related information was the internet (48.6%), followed by television (33%). In controlled models, higher health literacy scores were associated with higher education and income levels. The effects of television (β = 1,917), internet (β = 2,803), newspapers (β = 1,489), and smartphones (β = 1,974) as sources of health-related information were statistically significant in the general health literacy index model. Conclusions: Health literacy in Turkey reflects social inequalities. The model accounting for socioeconomic variables demonstrated the relevance of sources of health information to level of health literacy. These findings emphasize the importance of improving sources of health information to improve health literacy. [HLRP: Health Literacy Research and Practice. 2021;5(2):e109-e117.] Plain Language Summary: This is a cross-sectional study that is representative of the population of Turkey. We reported that health literacy scores were higher for people in higher levels of socioeconomic status. We showed that using the television, internet, newspapers, and smartphones as a source of health-related information is associated with health literacy even when accounting for socioeconomic variables.